Discrepancies between validated GC‐FID and UHPLC‐DAD methods for the analysis of Δ‐9‐THC and CBD in dried hemp flowers. Issue 10 (15th August 2022) - Duchateau, Céline; De Leersnijder, Cedric; Barhdadi, Sophia; Canfyn, Michaël; De Braekeleer, Kris; Deconinck, Eric
Abstract: Herbal products for smoking containing cannabidiol (CBD) are available as "low‐tetrahydrocannabinol cannabis products" in most EU countries. In Belgium, Δ9‐tetrahydrocannabinol (THC) content of these products must be less than 0.2% w/w, which is also the limit for agricultural hemp. For agricultural hemp, the official and only valid method for European regulators is gas‐chromatography coupled to flame ionization detector (GC‐FID). There is no such method, for smoking products. Many of these herbal for smoking products are analyzed as part of their quality control and have certificate of analysis. During surveillance by official labs, discrepancies were seen between the official results and the certificate of analysis. In this study, a GC‐FID method based on the European method and an ultra‐high‐performance liquid chromatography coupled to diode array detection (UHPLC‐DAD) method were validated and applied for samples analysis in order to investigate these discrepancies. The GC‐FID method shows better results for the validation parameters; notably, it has β‐expectation tolerance limits within 10% with a β value of 95% while the validated UHPLC‐DAD method has β‐expectation tolerance limits within 15% with a β value of 90%. Furthermore, the other parameters evaluated are generally better with the GC‐FID method. The statistic t test shows that the difference between both methods was significantly different for total‐THC, but not significantly different for the total‐CBD. The authors state that, as for agricultural hemp, the GC‐FID method is to be preferred for the analysis of THC and CBD in products for smoking. Abstract : THC in low‐THC cannabis smoking products containing CBD and agricultural hemp must be less than 0.2% w/w. GC‐FID method based on the European method and UHPLC‐DAD method were applied for samples analysis to investigate discrepancies shown in certificate of analysis and during surveillance by official labs.